Insights into severe 5,10-methylenetetrahydrofolate reductase deficiency: molecular genetic and enzymatic characterization of 76 patients - Burda, Patricie; Schäfer, Alexandra; Suormala, Terttu; Rummel, Till; Bürer, Céline; Heuberger, Dorothea; Frapolli, Michele; Giunta, Cecilia; Sokolová, Jitka; Vlášková, Hana; Kožich, Viktor; Koch, Hans Georg; et al. (Human mutation, 2015)
5,10-Methylenetetrahydrofolate reductase (MTHFR) deficiency is the most common inherited disorder of folate metabolism and causes severe hyperhomocysteinaemia. To better understand the relationship between mutation and function, we performed molecular genetic analysis of 76 MTHFR deficient patients, followed by extensive enzymatic characterization of fibroblasts from 72 of these. A deleterious mutation was detected on each of the 152 patient alleles, with one allele harboring two mutations. Sixty five different mutations (42 novel) were detected, including a common splicing mutation (c.1542G>A) found in 21 alleles. Using an enzyme assay in the physiological direction, we found residual activity (1.7%-42% of control) in 42 cell lines, of which 28 showed reduced affinity for nicotinamide adenine dinucleotide phosphate (NADPH), one reduced affinity for methylenetetrahydrofolate, five flavin adenine dinucleotide-responsiveness, and 24 abnormal kinetics of S-adenosylmethionine inhibition. Missense mutations causing virtually absent activity were found exclusively in the N-terminal catalytic domain, whereas missense mutations in the C-terminal regulatory domain caused decreased NADPH binding and disturbed inhibition by S-adenosylmethionine. Characterization of patients in this way provides a basis for improved diagnosis using expanded enzymatic criteria, increases understanding of the molecular basis of MTHFR dysfunction, and points to the possible role of cofactor or substrate in the treatment of patients with specific mutations.
Keywords: stabilita proteinů; kinetika; alely; Muscle Spasticity; Homocystinuria; jednonukleotidový polymorfismus; Alleles; homocystinurie; Introns; alternativní sestřih; methylenetetrahydrofolate; homocystinuria; Exons; mutace; Methylenetetrahydrofolate Reductase (NADPH2); Protein Stability; Enzyme Activation; Polymorphism, Single Nucleotide; genetické asociační studie; psychotické poruchy; Alternative Splicing; Humans; Mutation; methylentetrahydrofolátreduktasa (NADPH2); Fibroblasts; aktivace enzymů; Kinetics; MTHFR; introny; enzyme kinetics; Genetic Association Studies; Psychotic Disorders; svalová spasticita; exony; lidé; fibroblasty